METACONTINGENCIES DESCRIBED IN LAW 11343 OF 2006 OF THE BRAZILIAN ANTIDRUG SYSTEM - PAOLA ESPOSITO DE ALMEIDA; Bruno Vieira (Psicologia em Estudo, 2025)
The objective of this study was to identify the metacontingencies described in Law 11.343/2006, which addressed drug use prevention, health promotion, the social reintegration of users, and suppression of drug trafficking in Brazil. For the analysis of the Law, its articles were categorized to identify behavioral control contingencies that were either complete or incomplete. A contingency was considered complete if it specified all of the antecedents, responses, and consequences planned to change behaviors related to drug use and trafficking, and incomplete if it specified only part of these. The identified contingencies address the following themes: 1 – Context selecting the other contingencies; 2 – Contingencies of health care, prevention, and social reintegration; 3 – Contingencies for suppressing drug trafficking and production; and 4 – Contingencies for judging individuals and seizing assets derived from trafficking. A majority of complete contingencies were identified regarding the addressed themes. However, imprecise criteria were also identified for distinguishing between drug dealers and users, as well as for recording incidents. Additionally, there was an absence of positive reinforcement contingencies for behaviors alternative to trafficking, and the intervention proposals focused on total abstinence and punishment based on the temporary removal of traffickers and users from social interaction without addressing other environmental conditions that determine trafficking or use. The analysis reveals social control strategies based on coercive control as an educational practice. The inefficiencies of these strategies and the need for new regulations to be implemented and evaluated are discussed.